2012
DOI: 10.3892/ol.2012.747
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cytotoxic effects of recombinant human adenovirus p53 and radiation at various time points in A549 lung adenocarcinoma cells

Abstract: Abstract. The aim of this study was to evaluate the effects of recombinant human adenovirus p53 (rAd-p53; Gendicine) transfection and radiation at various time points following transfection. Cytotoxic effects and p53 protein expression levels were analyzed. rAd-p53 containing the human wild-type p53 gene was introduced into the human lung adenocarcinoma cell line A549, and cells were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The wild-type p53 gene (wt-p53) influences cell survival and the response to radiation-induced DNA damage. The studies (Hirao et al 2000; Ma et al 2012) found activated p53 transcription promotes can lead to cell cycle arrest, DNA repair, tumor cell apoptosis, and even killing effect on tumor cells. A previous study (Kandioler et al 2002) suggested that patients were less sensitive to RT if the function of wt-p53 lost, and RT combined with rAd-p53 may increase the sensitivity in vivo and in vitro studies (Shiomitsu et al 2008; Gudkov and Komarova 2003; Cuddihy and Bristow 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type p53 gene (wt-p53) influences cell survival and the response to radiation-induced DNA damage. The studies (Hirao et al 2000; Ma et al 2012) found activated p53 transcription promotes can lead to cell cycle arrest, DNA repair, tumor cell apoptosis, and even killing effect on tumor cells. A previous study (Kandioler et al 2002) suggested that patients were less sensitive to RT if the function of wt-p53 lost, and RT combined with rAd-p53 may increase the sensitivity in vivo and in vitro studies (Shiomitsu et al 2008; Gudkov and Komarova 2003; Cuddihy and Bristow 2004).…”
Section: Discussionmentioning
confidence: 99%
“…76,94 These enhancements are achieved primarily as a result of p53-mediated autophagy and apoptosis. 74,119,120,123,124,128,[166][167][168][169][170] In addition to synergistic effects on chemo-or radiotherapy, Gendicine could be used to augment immunotherapy. Ad-p53 gene therapy enhanced LAK immunotherapy in the treatment of HNC.…”
Section: Enhancing Other Therapiesmentioning
confidence: 99%
“…P53 is one of the most popular genes which has been studied extensively in the field of tumour biology [7][8][9]. While it was not until 1997 did we discover its sibling -p63.…”
Section: Introductionmentioning
confidence: 99%